(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Mobile marketing has been seen as a modern marketing tool that has offered businesses modern ways to do business. The marketing activities carried out via mobile devices allow advertisers to connect directly, irrespective of their geographic location, with potential customers. In recent times mobile advertising has been identified as one of the best ways to cope and communicate with customers directly. A cell phone is known to many people as one of the few other inviolate personal spaces to connect while socialize and at the same time they can still maintain control of the use of their mobile phones. Salespeople should take account of safety and privacy needs of customers in the creation of a marketing strategy for this purpose. Marketers should balance the participation of customers in their marketing mix and the achievement of the marketing campaign objectives. To order to do this, advertisers need to consider the factors that affect consumers’ acceptance of advertising across mobile phones, such as promotions and customer attitudes. The study looks at customer perceptions towards mobile publicity applications in India, which were launched in the near future as businesses understand the value of mobile publicity and spend more in mobile marketing apps.